Rapid determination of a stable glycated hemoglobin, s-A1c, by HPLC - MIZUNO, Masako; MIURA, Junkichi; ITO, Masahito; TOCHIGI, Kenji (BUNSEKI KAGAKU, 1991)
Glycated hemoglobins (GHb) are composed of A1a, A1b, labile-A1c (1-A1c), stable-A1c (s-A1c) and others. The concentration of s-A1c can be used as an index of the average blood glucose value for the preceding 2 months. Therefore, determination of s-A1c is useful for the assessment of long-term control of diabetes mellitus. A rapid analysis method of s-A1c by HPLC was discussed. Packings with 5 μm and 3.5 μm diameter polymethacrylate gel modified with carboxymethyl groups, were prepared, and a correlation between particle diameter of the packings and chromatographic performances, such as number of theoretical plates (N), retention time (tR), pressure drop (ΔP) were studied. N increased as the particle diameter of packings was decreased. The N for s-A1c by linear gradient elution was 2× 103 plates for 3.5 μm diameter packing, which was five times larger than that of 5 μm diameter packings. Using 3.5 μm packings, s-A1c was well separated from 1-A1c by the optimization of analytical conditions, such as the concen-tration of the initial eluent. Using the column (4.6 mm i.d. × 35 mm) packed with 3.5 μm packings, six hemoglobin components, A1a, A1b, HbF, 1-A1c, s-A1c and A0, were separated in a 3.5 min cycle by three step gradient elution, thereby reducing analysis time.